Pengendalian Biaya Produksi dalam Manufaktur: Teknik dan Tantangan - Ella Oktavinata Syahputri; Sulvio Berlusconi Sihombing; Nurhaliza Nurhaliza; Irma Wati; Mariana Mariana (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2025)
Controlling production costs in manufacturing is a crucial aspect that influences a company's efficiency and profitability. This research discusses various strategies and best practices in cost control, including analysis of raw material, labor and overhead costs. By implementing lean manufacturing principles, companies can identify and reduce waste, and increase productivity. Additionally, the use of technology and automation can contribute to long-term cost reduction. Implementation of a quality control system that has also been proven to reduce defect costs and increase customer satisfaction. Through regular performance evaluations and continuous innovation, companies can optimize production processes and achieve competitive advantage. This research is expected to provide insight for practitioners and academics in understanding the importance of controlling production costs in manufacturing.